CONTAMINATION OF SOIL IN DOG TRAINING CENTER OF RUSSIA IN PERM REGION OF HELMINTHES EGGS AND METHOD OF ITS DISINFECTION - T. N. Sivkova; M. V. Hazova (Российский паразитологический журнал, 2019)
Objective of research is investigation of level of soil contamination on the territory of Dog training service Center State institution of Home Office of Russia in Perm region by helminthes in warm period and activity of several disinfectants in different concentrations to parasite eggs in vitro. Materials and methods. Parasitological analysis of soil from different points of Dog Training Center was carried out by combined method. Investigations of activity of several disinfectants were carried out on example of noninvasive and invasive Toxocara canis eggs in vitro by direct addition and by addition to samples of soil. Results and discussion. Soil samples were collected from 13 points of the Dog Training Center: area for walk adult dogs, area for training to special program, two areas for walk puppies, quarantine area, central training area, passages between enclosures and glade with forest territory. The investigation of soil examples revealed presence of free nematodes and eggs of dog’s parasites: Toxocara canis, Ancylostoma caninum, Uncinaria stenocephala, Physaloptera spp., Capillaria sp., Strongiloides vulpis. Maximal level of infection was observed in May and minimal one - in April. At the second step of our work we analyzed effect of disinfectants from different chemical groups to T. сanis eggs. Preparations on base of chlorhexidinedigluconate 20 % and ethanol 70 %, quaternary ammonium compound alkyldimethilbenzilammonium chloride 10%, polyhexamethilenguanidine hydrochloride 1 % and carbamide, alkyldimethilbenzilammonium chloride 30 %, glyoxalin 5 %, gluten aldehyde 0,5 %, 17 % peracetic acid - 20 % peroxide, 3 % of active chlorine and formalin in 10 % and 40 % concentrations . Microscopic investigation was revealed that noninvasive T. canis eggs were destroyed only by effect of 2 % solution of preparation on base 17 % peracetic acid - 20 % peroxide and 3 % of active chlorine. Invasive eggs were not destroyed even extremely high doses of investigated solutions. Preparation on 17 % peracetic acid - 20% peroxide has not expressed smell but in big concentrations dries skin, therefore it is more effective to helminthes eggs and has better organoleptic characteristics. It is more suitable for soil disinfection in Dog training Center.